Principles for a names-based cyberinfrastructure to serve all of biology - Patterson, David J.; Faulwetter, Sarah; Shipunov, Alexey (Zootaxa, 2008)
The rapidly growing amount of biological data on the internet and the increasing need for large-scale analyses mandate improvements to the management of taxon-centric information. This information, traditionally managed by taxonomists, is now transforming into a web-based infrastructure. The complexity and narrative quality of the biological sciences require an information management framework that is sensitive to the scale, richness, character, and heterogeneity of the discipline. Given that the names of organisms offer us a nearly universal system for indexing biological data objects, a names-based cyberinfrastructure has the capacity to index the totality of available biological information and to aggregate taxon-centric data over a broad scale. In order to serve its role, this infrastructure should incorporate thirteen principles that are proposed here.